Primary Dealers in Government Securities - Arnone, Marco; Ugolini, Piero (Washington, D.C. : International Monetary Fund, 2005)
In the past 10 years a growing number of countries have established or began establishing a primary dealer system. This paper discusses the role of primary dealers, as well as theoretical, operational, and technical issues related to the establishment of a primary dealer system, in the overall management of public debt for countries that may be considering taking this step. Drawing on a 2001 survey of country practices, the paper discusses the rationale, costs and benefits, and key prerequisites, as well as selection criteria, obligations, and privileges of a primary dealer system. It also attempts to determine the conditions under which a primary dealer system would make a positive contribution to the functioning and development of the government securities market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet